2011
DOI: 10.1080/00222348.2011.610252
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organoclay on Microstructure Development and Rheological Properties of Poly(Butylene Terephtalate)/Epoxy/Organoclay Hybrid Systems

Abstract: The main objective of the present work was to study the role of organoclay on the microstructure development and rheological properties of poly(butylene terephtalate)/ epoxy/organoclay (Cloisite R 30B) hybrid nanocomposites. The effects of feeding order and curing of the epoxy were also investigated. The hybrid nanocomposite samples were prepared by melt compounding in a laboratory internal mixer at a temperature of 240 • C. The samples were prepared by three feeding routes; (1) simultaneous feeding, (2) PBT/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…From different types of nano-reinforcements available for polymers, nanoclay has attracted the greatest interest due to the ability of the silicate particles to disperse into individual layers. It has been shown that the presence of small amount of organoclay in the polymer blends in addition to reinforcing effect can also act as compatibilizing agent and cause substantial change in the size of dispersed domains (Fenouillot et al, 2009;Kontopoulou et al, 2007;Salehi et al, 2012). Wang et al (2003) showed that in PP/PS system, PS particle size is greatly decreased by the addition of organoclay.…”
Section: Introductionmentioning
confidence: 97%
“…From different types of nano-reinforcements available for polymers, nanoclay has attracted the greatest interest due to the ability of the silicate particles to disperse into individual layers. It has been shown that the presence of small amount of organoclay in the polymer blends in addition to reinforcing effect can also act as compatibilizing agent and cause substantial change in the size of dispersed domains (Fenouillot et al, 2009;Kontopoulou et al, 2007;Salehi et al, 2012). Wang et al (2003) showed that in PP/PS system, PS particle size is greatly decreased by the addition of organoclay.…”
Section: Introductionmentioning
confidence: 97%
“…Email: Bigdeli.fiber2010@yahoo.com During the last decade, considerable research activities have been directed toward using nanoparticles as interfacial agent as well as reinforcement in polymer blends (Elias, Fenouillot, Majeste, & Cassagnau, 2007;Lee, Kontopoulou, & Park, 2010). From many types of nanoreinforcements available for polymers, nanoclay has attracted the greatest interest due to the ability of the silicate particles to disperse into individual layers (Hong, Namkung, Ahn, Lee, & Kim, 2006;Salehi, Nazockdast, & Pircheraghi, 2012). As a result, they can influence the structural development of blends during melt processing and cause substantial change in the size of dispersed domains.…”
Section: Introductionmentioning
confidence: 98%
“…However, it is difficult to attain this objective in presence of in-organic silicate layers, particularly in immiscible blends [34][35][36].…”
Section: Introductionmentioning
confidence: 99%